Event-related potential measures of stimulus change detection during wakefulness and sleep onset. - Sabri, Merav. (University of Ottawa (Canada), 2001)
The Mismatch Negativity (MMN), an auditory event-related potential (ERPs) reflecting the detection of stimulus change, was recorded during wakefulness and sleep onset. In Experiment l, a 1000 Hz standard stimulus was presented every 600 ms. On 20% of the trials, the standard was changed randomly to either a large 2000 Hz (p = .10) or a small 1100 Hz (p = .10) deviant. During alert wakefulness (reading a book), a long-lasting MMN was elicited by presentation of both the small and the large deviant. During relaxed wakefulness (when the subject was asked to fall asleep) and Stage 2 sleep, the MMN to the large deviant, albeit attenuated, remained statistically significant. To test the hypothesis that sensory memory fades rapidly during sleep, Experiment 3 employed a very rapid rate of stimulus presentation. Experiment 2 was used to identify the optimal stimulus parameters for that test by examining the interactive effects of stimulus probability and stimulus presentation rate on the MMN during wakefulness. Auditory stimuli were 1000 Hz standard and 1100 Hz deviant. Stimulus probability was varied across stimulus-onset asynchronies (SOAs) of 150, 600, and 2400 ms. A long-lasting MMN was evident in all conditions except at the longest SOA (2400 ms). When the SOA was 150 ms, the largest MMN was elicited to the lowest deviant probability. In Experiment 3, a long-lasting MMN was elicited in alert wakefulness to either a small deviation (1100 Hz, p = .033) or a large deviation (2000 Hz, p = .033) from the standard (1000 Hz) in auditory frequency. SOA was 150 ms. A long-lasting MMN to the large deviant was observed during relaxed wakefulness, Stage 1 sleep, and non-REM sleep. The results of these experiments support the hypothesis that the MMN comparison system is at least partially automatic. It can be elicited during non-REM sleep, at least to large deviations in auditory frequency. The MMN following a small deviant is, however, difficult to observe during Stage 1 sleep or even as soon as relaxed wakefulness. It is possible that, during sleep onset, cortical encoding of both standard and deviant stimuli is weakened because of prior thalamic inhibition of sensory input.
Keywords: Psychology, Physiological.